Gong Kebyar Gamelan Music and Red-Blue LED (Light Emitting Diode) Improve the Growth and Productivity of Pakcoy Mustard (Brassica rapa L.) - Sigmarawan, Gede Teguh; Wijaya, I Made Anom S.; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
Growth and productivity of plants will occur if plants get light, carbon dioxide, water and nutrients that are sufficient for photosynthesis. In this study, pakcoy mustard was treated by combination of gong kebyar gamelan music and LED to determine its effect on the growth and productivity of pakcoy mustard, and determine the treatment that produced the best growth and productivity. The music is given for 3 hours starting at 09.00 - 12.00. LED light given for 20 hours starting at 06.00 - 02.00. The LEDs used include white, red-blue and red-white-blue. The variables observed include plant height, canopy area, leaves greenness, root length, wet weight and biomass of shoot and root. The result of the ANOVA analysis showed that the combination of gong kebyar gamelan music and white LED treatment had a negative effect, while the combination of gong kebyar gamelan music and red-blue, as well as red-white-blue LED treatment had a positive effect on the growth and productivity of pakcoy mustard. The combination of gong kebyar gamelan music and red-blue LED treatment produced the highest value on plant height (27.176 cm), canopy area (1457.59 cm2), greenness leaves (160.03), root length (23.6 cm), shoot and root wet weight (91.68 g and 5.26 g), and shoot and root biomass (4.63 g and 0.42 g). It can be concluded that the combination of gong kebyar gamelan music and red-blue LED treatment improved the growth and productivity of pakcoy mustard.